The angiotensin converting enzyme gene i/d polymorphism in elite polish and lithuanian judo players - Cieszczyk, P.; Maciejewska, A.; Sawczuk, M.; Ficek, K.; Eider, J.; Jascaniene, N. (Biology of Sport, 2010)
A common polymorphism in the angiotensin converting enzyme I gene (the ACE I/D variant) represents one of the first characterized and the most widely studied genetic variants in the context of elite athletes status and performance related traits. The aim of this study is to perform preliminary studies to analyze the possible importance of the ACE gene polymorphisms in elite Polish and Lithuanian judo players and sedentary individuals representing the possible relationships with genotype and physical performance. 28 male of elite Polish and Lithuania judo players were recruited for this study. For controls samples were prepared from 115 unrelated volunteers. DNA was extracted from the buccal cells donated by the subjects, and the PCR amplification of the polymorphic region of ACE gene contained either the insertion (I) or deletion (D) fragment was performed. Compared with sedentary controls, the frequency of I allele differ significantly from that found in judo player`s group: 60.7% vs. 44.3%, (p=0.02) and ACE genotype frequency amongst the whole athletes group (28.6% II, 64.3% ID, 7.1% DD) was also different from expected values (control group 19.1% II, 50.4% ID, 30.4% DD; p=0.019). Our investigation have proved the ACE I/D allele could be one of the factors influencing the elite endurance exercise performance. The research suggests that those most predisposed to judo are individuals with the allele distribution in the ACE gene that is most significant with regard to the duration of a fight, and not with regard to the character of the performed moves, as could be supposed.